Pengaruh Kemampuan Berbahasa Inggris dan Pemahaman Dasar Akuntansi terhadap Hasil Belajar MYOB pada Mata Kuliah Komputer Akuntansi - Wardiningsih, Reny (Lembaga Yasin AlSys, 2023)
MYOB (Mind Your Own Business) is a software program that is useful for users to make financial reports assisted by a computer system quickly, precisely and accurately. The purpose of this study was to determine the factors that influence MYOB learning outcomes in the Computer Accounting course, the factors used in this study were English language skills and a basic understanding of accounting. The approach used is a quantitative approach to the survey method. Sampling used a purposive sampling technique, namely sampling based on predetermined criteria. The sample results were 100 Computerized Accounting students at Mataram University of Technology to fill out a questionnaire. Data processing in this study used SPSS 26.00 by testing multiple linear regression. Hypothesis testing uses the F test, t test and R square test. The results obtained from the F test (6.202) with a significance level of 0.001 <0.05. This means that all the independent variables used in this study have an influence on MYOB learning outcomes in the Computer Accounting course. The results of the t test concluded that H1 and H2 were accepted. The results of the R Square test show that the independent variables explain 35.2% of the dependent variable, while 64.8% are explained by other variables outside this research model.